Study the corrosion inhibition of mix of caffeine and iodua for CT3 steel in 1M HCl solution by electrochemical methods - Thao, Truong (VNU Journal of Science: Natural Sciences and Technology, 2017)
Abstract: Corrosion inhibition of mild carbon steel, CT3,  in 1.0 M HCl solution by iodide  (with different concentrations, from 0.1g/l to 5.0g/l), mix of caffeine and iodide was investigated by electrochemical methods and micro surface observations (SEM). Experiment result showed that: (1) as the concentration of iodide increases, the inhibition efficiency increases;  Iodide acts as a mix – type inhibitor but inhibits anodic reaction is predominant. (2) Mix of 1.0 g/l iodide ang caffeine acts as a typical mix – type inhibitor. the current densities of both of anodic and cathode are decline when concentration of caffeine is 1.0 g/l or more. Inhibition efficiency max is approximately 96% at concentration of 5.0 g/l caffeine, the inhibition efficiency maintained relatively stable within 5 days.